Fatigue damage analysis of a riveted steel overhead crane support truss. (November 2019) - Lehner, P.; Krejsa, M.; Pařenica, P.; Křivý, V.; Brožovský, J.
Highlights: An overhead crane track truss structure model is constructed. Load history is described stochastically using the Monte Carlo method. Stress ranges are derived by rainflow counting and the Palmgren–Miner rule. The fatigue damage of an existing riveted connection is investigated. The remaining life of the riveted connection is then determined. Abstract: A method is proposed to evaluate the residual life of existing steel structures in terms of fatigue damage. The proposed method is demonstrated on the assessment of selected elements in a nearly 100-year old exterior riveted crane support truss. The Monte Carlo method is used to generate a time-dependent load based on the operation of the overhead crane, and detailed numerical modelling based on rainflow counting and the Palmgren-Miner rule to assess their fatigue resistance and estimate their residual life is evaluated and discussed. This study provides a novel approach to the reliability assessment of riveted joints stressed by cyclic loading and stochastic modelling of the load history of existing structures.